2007
DOI: 10.1093/cercor/bhm012
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Protein and Neuronal Activity Markers Define Regional Architectonic Parcellation in the Mouse Visual Cortex

Abstract: This study was designed to assess the chemoarchitectural organization and extent of the mouse visual cortex. We used nonphosphorylated neurofilament protein, a neuronal marker that exhibits region-specific cellular and laminar patterns, to delineate cortical subdivisions. A comprehensive analysis demonstrated that pyramidal and nonpyramidal neurons expressing neurofilament proteins display striking laminar and regional patterns in the mouse visual cortex permitting the delineation of the primary visual cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 74 publications
11
88
1
Order By: Relevance
“…The manatee mainly exhibited light staining in layers IIIc and parts of VI, and heavy staining in layer V, while cetaceans have heavy staining in the combined layer IIIc/V . This pattern differs from what is seen in primates, rodents and carnivores, where staining is more diffusely distributed throughout the cortex wherever there are pyramidal neurons [Campbell and Morrison, 1989;Chaudhuri et al, 1996;Hof et al, 1996;Nimchinsky et al, 1997;Preuss et al, 1997;Budinger et al, 2000;Tsang et al, 2000;Van der Gucht et al, 2001;Sherwood et al, 2004;Baldauf, 2005;Boire et al, 2005;Bourne et al, 2005;Hof and Sherwood, 2005;Bourne et al, 2007;Van der Gucht et al, 2007] but is similar to what is also observed in afrotherians, xenarthrans, monotremes and marsupials Hassiotis et al, 2005;Sherwood et al, 2009]. Primates, rodents and carnivores also have different patterns of NPNFP-ir neuron distribution in different cortical areas [Campbell and Morrison, 1989;Campbell et al, 1991;Hof and Nimchinsky, 1992;Budinger et al, 2000;Van der Gucht et al, 2001, which is not as clearly variable across the cortex in afrotherians, xenarthrans, monotremes and marsupials Ashwell et al, 2005;Hassiotis and Paxinos, 2004;Hassiotis et al, 2005;Sherwood et al, 2009].…”
Section: Possible Factors Influencing Manatee Neuron Types and Districontrasting
confidence: 55%
“…The manatee mainly exhibited light staining in layers IIIc and parts of VI, and heavy staining in layer V, while cetaceans have heavy staining in the combined layer IIIc/V . This pattern differs from what is seen in primates, rodents and carnivores, where staining is more diffusely distributed throughout the cortex wherever there are pyramidal neurons [Campbell and Morrison, 1989;Chaudhuri et al, 1996;Hof et al, 1996;Nimchinsky et al, 1997;Preuss et al, 1997;Budinger et al, 2000;Tsang et al, 2000;Van der Gucht et al, 2001;Sherwood et al, 2004;Baldauf, 2005;Boire et al, 2005;Bourne et al, 2005;Hof and Sherwood, 2005;Bourne et al, 2007;Van der Gucht et al, 2007] but is similar to what is also observed in afrotherians, xenarthrans, monotremes and marsupials Hassiotis et al, 2005;Sherwood et al, 2009]. Primates, rodents and carnivores also have different patterns of NPNFP-ir neuron distribution in different cortical areas [Campbell and Morrison, 1989;Campbell et al, 1991;Hof and Nimchinsky, 1992;Budinger et al, 2000;Van der Gucht et al, 2001, which is not as clearly variable across the cortex in afrotherians, xenarthrans, monotremes and marsupials Ashwell et al, 2005;Hassiotis and Paxinos, 2004;Hassiotis et al, 2005;Sherwood et al, 2009].…”
Section: Possible Factors Influencing Manatee Neuron Types and Districontrasting
confidence: 55%
“…Significance was set at p Ͻ 0.05. Diamond et al, 1999;Paxinos and Franklin, 2001;Grove and Fukuchi-Shimogori, 2003;Van der Gucht et al, 2007). Green shading is for primary somatosensory cortex (BF, barrel field; FL, forelimb; HL, hindlimb; LL, lower lip; No, nostril; Rv, rostral vibrissae; Tr, trunk; UL, upper lip), blue shading is for visual cortex and red shading for motor cortex.…”
Section: Methodsmentioning
confidence: 99%
“…8 ; see list of abbreviations). Recent architectonic studies in the mouse have further divided this medial cortex into a V2M caudally and 4 rostromedial fields (RM1-4) using nonphosphorylated neurofilament protein [ Van der Gucht et al, 2007].…”
Section: Organization Of Visual Cortexmentioning
confidence: 99%